Proceedings of the 2014 Workshop on Multimodal, Multi-Party, Real-World Human-Robot Interaction 2014
DOI: 10.1145/2666499.2666502
|View full text |Cite
|
Sign up to set email alerts
|

Attention Detection in Elderly People-Robot Spoken Interaction

Abstract: In many human-robot social interactions, where the robot is to interact with only one human throughout the interaction, the "human" side of a conversation is very likely to interact with other humans present in the same room and temporarily loses the focus on the main interaction. These humanhuman interactions can be a very brief chat or a pretty long discussion. To effectively build a human-robot spoken interaction system, one should enable the robot to be aware of the situations where it is (or it is not) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…We can confirm the finding by Sehili et al (2014) for a positive relationship between neuroticism and an anthropomorphic perception of the robot (r 0.22, p 0.035). In contrast to Looije et al (2010), we cannot confirm any relationship between self-reported conscientiousness of a participant and the perceived sociability of a robot.…”
Section: Population Statisticssupporting
confidence: 84%
“…We can confirm the finding by Sehili et al (2014) for a positive relationship between neuroticism and an anthropomorphic perception of the robot (r 0.22, p 0.035). In contrast to Looije et al (2010), we cannot confirm any relationship between self-reported conscientiousness of a participant and the perceived sociability of a robot.…”
Section: Population Statisticssupporting
confidence: 84%
“…The limitation in this study is that it has been done only with the available data of the students through a multimedia slide presentation. Voice examination and the head-turning system were introduced by the author in the paper [29], where the author used a mixture of when speaking among persons, where the detection of head-turning sector's success rate was 87.7%. The ROMEO2 project has been implemented to create a human-robot interaction system whose job is to work as an assistant to the people with loss of autonomy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies have examined joint attention between human user and robot during spoken interaction [15] [16] [17]. In [18], an audio-visual social interaction corpus was collected and annotated to investigate behaviour patterns of robot users and their attention while interacting with the robot. More recently, the timing of interaction has been explored to design robots that can embody these behavioural resources.…”
Section: B User Interfacesmentioning
confidence: 99%